Relationship between stress-related psychosocial work factors and suboptimal health among Chinese medical staff: a cross-sectional study. Issue 3 (6th March 2018) - Liang, Ying-Zhi; Chu, Xi; Meng, Shi-Jiao; Zhang, Jie; Wu, Li-Juan; Yan, Yu-Xiang
Abstract : Objectives: The study aimed to develop and validate a model to measure psychosocial factors at work among medical staff in China based on confirmatory factor analysis (CFA). The second aim of the current study was to clarify the association between stress-related psychosocial work factors and suboptimal health status. Design: The cross-sectional study was conducted using clustered sampling method. Setting: Xuanwu Hospital, a 3A grade hospital in Beijing. Participants: Nine hundred and fourteen medical staff aged over 40 years were sampled. Seven hundred and ninety-seven valid questionnaires were collected and used for further analyses. The sample included 94% of the Han population. Main outcome measures: The Copenhagen Psychosocial Questionnaire (COPSOQ) and the Suboptimal Health Status Questionnaires-25 were used to assess the psychosocial factors at work and suboptimal health status, respectively. CFA was conducted to establish the evaluating method of COPSOQ. A multivariate logistic regression model was used to estimate the relationship between suboptimal health status and stress-related psychosocial work factors among Chinese medical staff. Results: There was a strong correlation among the five dimensions of COPSOQ based on the first-order factor model. Then, we established two second-order factors including negative and positive psychosocial work stress factors to evaluate psychosocial factors at work, and the second-order factor model fit well. The high score in negative (OR (95% CI)=1.47 (1.34 to 1.62), P<0.001) and positive (OR (95% CI)=0.96 (0.94 to 0.98), P<0.001) psychosocial work factors increased and decreased the risk of suboptimal health, respectively. This relationship remained statistically significant after adjusting for confounders and when using different cut-offs of suboptimal health status. Conclusions: Among medical staff, the second-order factor model was a suitable method to evaluate the COPSOQ. The negative and positive psychosocial work stress factors might be the risk and protective factors of suboptimal health, respectively. Moreover, negative psychosocial work stress was the most associated factor to predict suboptimal health.